When Civilians "Cross The Line": The International And Islamic Law Perspectives" - Norfadhilah Mohd Ali; Muhammad Najib Abdullah; Fadhlina Alias; Rodziana Mohamed Razali; Ahmad Zaki Salleh (Centre for Promoting Ideas, USA, 2024)
The protection of civilians is one of the most integral aspects of international humanitarian law. Civilians are defined in the Geneva Convention Relative to the Protection of Civilian Persons in Time of War to include persons taking no active part in the hostilities, including members of armed forces who have laid down their arms and those considered hors de combat by virtue of sickness, wounds, detention, or any other cause. According to international law, civilians shall in all circumstances be treated humanely, without any adverse distinction founded on race, colour, religion or faith, sex, birth or wealth, or any other similar criteria. It is however a growing concern in international humanitarian law as military forces claim that certain attacks on civilians are justified, be it due to „military advantage‟, or that the civilians themselves have in one way or another, participated in the warfare. In such situations, both the armed forces and the law would have to determine whether the “civilians” are still civilians at the point of attack, or "civilians" who have lost their characteristics as civilians. This paper will discuss on the demarcation between the legal status of a civilian and the justifications of the claim to lift civilian characteristics from civilians in different situations, as well as issues of „active‟, „direct‟ and „sympathetic‟ involvement of civilians in hostilities. In doing so, both the international law and Islamic law point of view will comparatively be examined.